2021
DOI: 10.3389/fvets.2021.673577
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Viral Diarrhea Virus in Cattle From Mexico: Current Status

Abstract: Bovine viral diarrhea (BVD) is an infectious disease, globally-distributed, caused by bovine Pestiviruses, endemic of cattle and other ruminant populations. BVD leads to significant economic losses to the cattle industry due to the wide range of clinical manifestations, including respiratory and gastrointestinal diseases and reproductive disorders. Within the Pestivirus genus of the family Flaviviridae three viral species are associated with BVD; Pestivirus A (Bovine viral diarrhea virus 1, BVDV-1), Pestivirus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Collectively, these data would suggest that the exposure may be associated with vaccination rather than natural exposure to BVDV. Given that, currently, vaccination is considered good livestock practice, but no data are available to determine the actual vaccine usage ( 20 ), the route of pestivirus exposure cannot be conclusively determined, although the three Mexican states (Coahuila, Nuevo Leon, and Tamaulipas) that border the permanent quarantine zone make up over 30% of the Mexico cattle exports, which, in turn, can lead to an increased risk for managed or processed Mexican cattle escaping enclosures or breaking free from larger groups ( 4 , 21 ). During drought periods, ranchers may move their animals closer to the river (Rio Grande) in search of forage, which may facilitate cattle unintentionally crossing the river while grazing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Collectively, these data would suggest that the exposure may be associated with vaccination rather than natural exposure to BVDV. Given that, currently, vaccination is considered good livestock practice, but no data are available to determine the actual vaccine usage ( 20 ), the route of pestivirus exposure cannot be conclusively determined, although the three Mexican states (Coahuila, Nuevo Leon, and Tamaulipas) that border the permanent quarantine zone make up over 30% of the Mexico cattle exports, which, in turn, can lead to an increased risk for managed or processed Mexican cattle escaping enclosures or breaking free from larger groups ( 4 , 21 ). During drought periods, ranchers may move their animals closer to the river (Rio Grande) in search of forage, which may facilitate cattle unintentionally crossing the river while grazing.…”
Section: Discussionmentioning
confidence: 99%
“…The first study of BVD in Mexico was a serosurvey in 1975 based on 47 nonvaccinated animals with a clinical history of abortions, infertility, and respiratory signs and reported seropositivity of 75% ( 23 ). Subsequent seroprevalence studies of dairy cattle and beef cattle from multiple states reported seropositivity to range from ~47 to 80% ( 20 , 24 – 28 ). Therefore, in general, the seroprevalence rate in stray cattle tends to be lower than other seroprevalence surveys conducted in the United States and Mexico and provides further evidence of a more susceptible population of cattle that may cross country borders.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, active infection with BVDV subgenotype 1b was identified for the first time in Brazil’s two herds of dairy buffaloes [ 70 ]. Of interest, the virus has been detected in fetal bovine serum from Brazil, Australia, Canada, the United States, and Mexico [ 59 , 71 ]. Studies in Argentina showed high positivity against BVDV-1 and BVDV-2 in buffalo herds.…”
Section: Bovine Viral Diarrheamentioning
confidence: 99%
“…The genotyping classi cation for BVDV isolates can be implicated in disease control as diagnostics and vaccines that work well against homologous strains. Currently, the BVDV-1b is generally predominant subgenotype in the world, followed by BVDV-1a and 1c [10]. Turning to distribution of BVDV-2 subgenotype, BVDV-2a is the most prevalent globally, while subgenotpes 2b, 2c and 2d were just prevalent in European and Asian countries [7].…”
Section: Introductionmentioning
confidence: 99%